STANDARD MANUFACTURING PROCEDURE OF AJA PANCHAKA GHRITA - goswami.Jay; Kalsariya B.D; Zala U.U; Umrethiya B.L; Paneliya A.M (International Journal of Applied Ayurved Research, 2019)
There are many dosage forms described in Ayurveda by different Acharyas, Sneha Kalpana is one among them. Sneha Kalpana is widely described dosage form in Ayurvedic pharmaceutics under which Taila and Ghrita are prepared. Ghrita alleviates Pitta and Vata, is beneficial for Rasa, semen and Ojas, cooling, softening and improves voice and complexion. Aja Panchaka Ghrita is prepared with five products of goat that are Aja Ksheera, Aja Dadhi, Aja Ghrita, Aja Mutra and Aja Shakrita Rasa. Ayurveda is expanding globally and scientists all over the world attracting towards Ayurveda. It is our prime duty to develop basic standards at every step of drug preparation. Some Ayurvedic practitioners are using Ajapanchaka Ghrita for the treatment of Tuberculosis. But there is no any scientific data regarding its SMP (Standard Manufacturing Procedure) and anti-tuberculosis effectTreatment of any disease is depends upon quality and purity of the medicine. So in consideration of above all facts here Aja Panchaka Ghrita is to be taken to develop its SMP (Standard Manufacturing Procedure).